English, Class 08, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745165 2129771:9267C68M 4752638:DC656WJI
Keywords: SSEIP